PENGARUH PENAMBAHAN BAKAN BAKAR MINYAK JARAK (Jatropha Oil) DAN BIOADITIF TERHADAP PERFORMA DAN EMISI GAS BUANG PADA MESIN DIESEL - Walid Najibullah; Abdul Wahab; Ena Marlina (Jurnal Teknik Mesin, 2016)
Diesel engine is a kind of combustion where fuel is ignited by the high temperature gas is compressed. Comparison with the fuel-air mixture, the incoming air to be compressed in adiabatic so that the temperature becomes higher, then the air combined with sprayed oil slowly in a state of almost isobars. Biodiesel is an alternative fuel that can be used directly or blended with diesel fuel in diesel engines. The purpose of this research to study the characteristics of alternative fuel diesel engine (torque, power, specific fuel consumption, and exhaust emissions) on a standard diesel engine. The test is performed with experimental tests on diesel engines with biodiesel fuel 90% and the addition of castor oil 10%, while the percentage bioadditive as much as 0.5% and 9.5% castor oil on the stationary engine rev 200rpm. The results showed that the maximum value of 14.3 kg m torque, specific power of 28.6 kW at a constant 2000 rpm rotation and the needs of specific fuel 0.775 kg / kWh in a mixture of castor oil and biodiesel by 10% and 90%. While the lowest smoke gas opacity 23% on bioadditive mixture of clove oil on castor oil as much as 9.5% and 0.5%. Diesel engines with a constant rotation makes torque, effective power and specific fuel consumption is less than perfect, while the addition of castor oil and clove oil bioadditive of the fuel can lower the concentration of gas fumes in diesel engines.